Conservatism Moderates the Effects of Profitability, Leverage and Growth Opportunity on Cash Holding: Evidence in Indonesian Consumer Good Firms - Pristin Prima Sari; Sri Hermuningsih; Fuadhillah Kirana Putri; Risal Rinofah; Salma Novika Putri; Anisya Dewi Rahmawati (Fundamental and Applied Management Journal, 2026)
Cash holding have bad impact for firms if the lower cash holding the lower liquidity of payment. Cash holding conducted by cash and cash equivalent. Optimal cash holding strengthens streamline operational of firms. So that, cash holding controlled by conservatism which strengthen profitability, leverage and growth opportunity. Conservatism can help firm management to control their cash holding. Conservatism provide accrual of financial statement as firm action in financial decision. The aims of research such as conservatism strengthens the profitability, leverage and growth opportunity on cash holding.  The method such as quantitative using financial statement data listed in Indonesia Stock Exchange (IDX) with consumer goods sector in 2021-2025 as samples by using purposive sampling, then Moderated Regression Analysis (MRA) and SPSS 25 to analysis technique. The finding such as Conservatism, Leverage, Growth Opportunity, profitability simultaneously significant impact on cash holding. Conservatism and profitability partially significant impact on cash holding but leverage and growth opportunity do not have significant impact on cash holding. The conclusion are that Conservatism strengthens the profitability on cash holding but conservatism as negative moderation between growth opportunity and cash holding. Thus conservatism have no significant moderation between leverage on cash holding.